The Relationships between Living Conditions and Life Satisfaction of Elderly People in Istanbul - Lale Berkoz (European Regional Science Association (ERSA), 2014)
The rate of the elderly population increases rapidly throughout the world. The growth rate of the elderly population in the world is 2.1%, whereas the overall population growth rate is over 1.2 % (Mandiraoglu, 2010). The elderly population rate in the United States varies between 15% and 20 %. However, the elderly population rate in Turkey has not reached the level of developed western countries. Although the population rate of those who are 60 and over in Turkey was 5.9% in 1950, it has risen to 7.0% in 1990 and 8.4% in 2000. Today this rate is about 10%. For the coming of aging society, the life satisfaction for the elderly people are very important. Satisfaction is the sense of fulfillment resulting from meeting the needs and demands. Life satisfaction refers to the individual's positive evaluation of his/her life as a whole. Life satisfaction, in other words, subjective quality of life, is a major element of quality aging (TSI, 2004). Along with the health issues that arise with old age, the elderly also encounter problems adapting to the changing urban space, which has not been constructed considering their needs. By creating livable spatial environments, it is especially important to provide the elderly and the disabled with suitable, comfortable and safe living spaces. In this sense, considering universal designing criteria in creating urban strategies can help form and maintain healthy cities. There are a few studies analyzing the life quality of the elderly in Turkey. This study is aimed at investigating the relationships between the living conditions and life satisfaction of the elderly in Istanbul. In the scope of this study 410 questionnaires have been made in face to face interviews of elderly people in residential areas in the districts of Bakýrkoy, Kadýkoy and Besiktas. While selecting these samples, questionnaire quota has been applied proportional to the population of each district and elderly people population. The reason why these districts were selected is the rate of the elderly population in the related areas which is twice as much as the average of Istanbul.
Keywords: H13; 330; Life satisfaction; life quality; elderly people; Istanbul